2022
DOI: 10.1186/s12920-022-01292-y
|View full text |Cite
|
Sign up to set email alerts
|

mRNA and long non-coding RNA expression profiles of rotator cuff tear patients reveal inflammatory features in long head of biceps tendon

Abstract: Background This study aimed to identify the differentially expressed mRNAs and lncRNAs in inflammatory long head of biceps tendon (LHBT) of rotator cuff tear (RCT) patients and further explore the function and potential targets of differentially expressed lncRNAs in biceps tendon pathology. Methods Human gene expression microarray was made between 3 inflammatory LHBT samples and 3 normal LHBT samples from RCT patients. GO analysis and KEGG pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Besides, the hyperglycemic condition potentially promoted poor healing of rotator cuff because of inadequate production of several important cytokines or growth factors [29]. As for the gene expression profiling of patients with RCT, Ren et al [30] identified the differentially expressed lncRNAs in inflammatory long head of biceps tendon (LHBT), which may cause chronic RCT. Based on their results, they found that lncRNA-COL6A4P2, A2MP1 and LOC100996671 may act as a regulator in the process of the inflammation of LHBT in RCT patients through NFKB2/NF-kappa B signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the hyperglycemic condition potentially promoted poor healing of rotator cuff because of inadequate production of several important cytokines or growth factors [29]. As for the gene expression profiling of patients with RCT, Ren et al [30] identified the differentially expressed lncRNAs in inflammatory long head of biceps tendon (LHBT), which may cause chronic RCT. Based on their results, they found that lncRNA-COL6A4P2, A2MP1 and LOC100996671 may act as a regulator in the process of the inflammation of LHBT in RCT patients through NFKB2/NF-kappa B signaling pathway.…”
Section: Discussionmentioning
confidence: 99%